Palliative care in Ireland - Agnieszka Kmita, Dominika; Czarkowski, Wiktor Maria; Janecki, Marcin (Medycyna Paliatywna/Palliative Medicine, 2022)
Ireland’s aging society with coexisting increased multimorbidity and mortality means there is a greater demand for palliative care. It is dedicated to patients with terminal illnesses, as well as those with chronic diseases. Due to multiculturalism, access to such help should be equal and take interpersonal differences into account. The aim of this article is to describe the structure of Ireland’s palliative care, detailing levels of service provision, established goals, evidence of improvement, and funding. The base of the featured issue is “Adult Palliative Care Services, Model of Care for Ireland” released by the Health Service Executive in 2019. The main target of palliative care is easy access to service provision, which is adjusted to the patient’s needs and improves the their quality of life. This target can be achieved based on 8 foundations: planning care, providing carer support, integrating health care, specialist training, systems of patients’ information, quality improvement, research, and innovation. The available information allows us to conclude that palliative care in Ireland provides services on a high level and is continually developing. Cooperation of many organizations, implementation of new projects, and properly coordinated patient-oriented actions have resulted in one of the best palliative care services in the world.